Pengembangan produk yoghurt sinbiotik uwi ungu (Dioscorea alata var purpurea) sebagai pangan fungsional - Rosida Rosida; Sintha Soraya Santi (AGROINTEK, 2021)
Purple water yam had good prospect to be developed as functioonal food because it had high dietary fiber, inulin, antocyanin and antioxidant compunds. The aim of this research was to determine the physicochemical and sensoric characteristics of synbiotic yoghurt from cow’s milk and purple water yam extract using Lactobacillus bulgaricus, Streptococcus thermophilus and Bifidobacterium bifidum. This research used This research used Completely Randomized Design with factorial pattern which was consisted of 2 factors and 2 replications. Factor 1 is the proportion of cow’s milk : purple water yam extract (50:50, 40:60, and 30:70) and Factor 2 is concentration of Lactic acid bacteria (3%, 4% and 5%). ANOVA was employed to analyze the data. If there was asignificant diffence, it should be followed by Duncan’s Multiple Range Test (DMRT) at a significance level α=0.05. The result revelaed that the best treatment was the proportion milk: water yam extract (40:60) and 5% starter LAB, which produced synbiotic yoghurt with lactic acid bacteria total of 9.42 Log CFU/ml, lactic acid total 1.98%, dietary fiber content 3.85%. This synbiotic yoghurt had average hedonic score of taste 2.75, color 3.25, smell 3.50, texture 2.85, which means it was preferred by the pannels